Parameterized Kick Engine for R-SCUAD Robot - Nuryono Satya Widodo; Watra Arsadiando; Arif Rahman Muhammad Iqbalul; Faiq Hatta (IAES Indonesia Section, 2017)
Humanoid Robot Soccer is an implementation of technology in robotics area that has the ability to mimic human activity to play football. Kicking is one of many abilities that the robot must have to play football nicely. The ability to kick in a various kind of kick also needed to enhance it’s performance in the match.This research was conducted on a 20 degree of freedom humanoid robot soccer named R-SCUAD. The robot was equipped with 20 Dynamixel servo motors as the actuator, an arbotix-pro as a sub-controller and an Odroid XU4 as the main controller. The method developed in this research was based on Darwin-op framework with an enhancement especially on the kick engine. Experiment results showed that there was a corellations between the distance that the ball travelled due to a kick with leg the swing speed of the kick, it can be inferred that a greater swing speed value will yields a greater distance of ball travel. With the leg swing speed of 50 rpm generate average distance 36.58 cm while with a speed of 300 rpm generate an average distance of 329.62 cm. Result also showed that the balancing system developed based on kick angle computation was able to maintain the robot stability up to 25 ° of kick angle.